Transformasi Pendidikan Islam pada Masyarakat Samin di Blora Jawa Tengah: Penelitian - Siti Zumrotun Nisa; Muhammad Arif Syihabuddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the forms, processes, and roles of institutions and religious leaders in the transformation of Islamic education among the Samin community in Blora, Central Java. The Samin community is known as a traditional group that upholds honesty, simplicity, and peaceful coexistence. The research employs a qualitative ethnographic approach, using in-depth interviews, participatory observation, and documentation. Findings show that the transformation of Islamic education within the Samin society occurs gradually and through acculturation. The process begins with socio-cultural engagement by religious figures and continues with the introduction of Islamic values that align with the Samin way of life. Over time, the community has accepted both formal and non-formal Islamic education, such as TPQ and elementary school, and has actively participated in religious activities. This transformation is not only individual but also structural, as respected community leaders become bridges between local culture and Islamic teachings. These findings highlight the importance of a humanistic, dialogical, and culturally sensitive approach in implementing Islamic educational transformation within indigenous communities.